2021
DOI: 10.1021/acs.est.0c08805
|View full text |Cite
|
Sign up to set email alerts
|

Single-Atom Fe Catalyst Outperforms Its Homogeneous Counterpart for Activating Peroxymonosulfate to Achieve Effective Degradation of Organic Contaminants

Abstract: Recently, reactive iron species (RFeS) have shown great potential for the selective degradation of emerging organic contaminants (EOCs). However, the rapid generation of RFeS for the selective and efficient degradation of EOCs over a wide pH range is still challenging. Herein, we constructed FeN4 structures on a carbon nanotube (CNT) to obtain single-atom catalysts (FeSA-N-CNT) to generate RFeS in the presence of peroxymonosulfate (PMS). The obtained FeSA-N-CNT/PMS system exhibited outstanding and selective re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
127
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 290 publications
(129 citation statements)
references
References 65 publications
(105 reference statements)
2
127
0
Order By: Relevance
“…In contrast, the rate of degradation of 4‐CP changed significantly when diverse anions, cations, and NOM were introduced into the Fe NP /CN activated PMS system (Figures 4 b and S26), which shows that the degradation process of 4‐CP with SO 4 .− and . OH radicals is easily disturbed by the environmental substances [30] . More importantly, Fe 1 /CN achieved similar rates of degradation of 4‐CP in natural (tap water, the Poyang Lake water, and the Yangtze River water) and deionized waters (Figure 4 d), indicating its excellent practical application prospects.…”
Section: Figurementioning
confidence: 76%
“…In contrast, the rate of degradation of 4‐CP changed significantly when diverse anions, cations, and NOM were introduced into the Fe NP /CN activated PMS system (Figures 4 b and S26), which shows that the degradation process of 4‐CP with SO 4 .− and . OH radicals is easily disturbed by the environmental substances [30] . More importantly, Fe 1 /CN achieved similar rates of degradation of 4‐CP in natural (tap water, the Poyang Lake water, and the Yangtze River water) and deionized waters (Figure 4 d), indicating its excellent practical application prospects.…”
Section: Figurementioning
confidence: 76%
“…Usually, in a system dominated by high-valent Fe, the oxidation process will be ended with PMSO converted into PMSO 2 , and further degradation will not happen. [50][51][52] Therefore, we speculate that this process is not dominated by high-valence Fe.…”
Section: •−mentioning
confidence: 99%
“…In contrast, the rate of degradation of 4-CP changed significantly when diverse anions, cations, and NOM were introduced into the Fe NP /CN activated PMS system (Figures 4 b and S26), which shows that the degradation process of 4-CP with SO 4 C À and COH radicals is easily disturbed by the environmental substances. [30] More importantly, Fe 1 /CN achieved similar rates of degradation of 4-CP in natural (tap water, the Poyang Lake water, and the Yangtze River water) and deionized waters (Figure 4 d), indicating its excellent practical application prospects. As shown in Figure S27, the cyclic tests demonstrated that Fe 1 /CN is more stable than Fe NP /CN during the activation of PMS for the degradation of 4-CP.…”
Section: Methodsmentioning
confidence: 78%